Graphical user interface of ordinary differential equation solution with numerical method / Muhammad Ikhwan Azman - Azman, Muhammad Ikhwan (2018)
First and second order ordinary differential equations (ODE) can be solve by several numerical methods. Runge-Kutta (RK) is one of the most popular and accurate numerical method for solving ODE. There are several versions of RK available. In this research, several problems of first order ODE is selected to be solve using Runge-Kutta of fourth, fifth and sixth. A user friendly Graphical User Interface is also developed for ease of application for these RK versions